Análisis de la calidad de energía eléctrica aplicando la regulación ARCONEL 005-18 en la subestación de la CNEL EP Unidad de Negocios Santo Domingo. - Oña Moreno, Cristian José (2022)
This research document presents an analysis of the quality of electrical energy in the substation of the CNEL EP Santo Domingo business unit, with the purpose of proposing solutions focused on the quality attributes of the distributor, for which it has been taken as a proposal the identification of critical points in the distribution network of the substation through a classification method of natural cuts (Jenks), with which it is possible to visualize through the GWR geographically weighted regression tool in the ArcGIS 10.4 student version software, where the electrical parameters that fail to comply with the limits of product quality levels established by Regulation No. ARCONEL 005-18, were examined with three-phase energy quality analyzers, these electrical indicators will be reflected in particular a non-compliance level of 11.32 % at voltage levels, 43.78% voltage harmonic distortion, at fast disturbances s of voltage or FLICKERS 4.02%, while the greatest impact is generated by low power factor representing 85.54% of the distribution transformers analyzed and finally the voltage imbalance representing 68.67% of non-compliance in this indicator, for this purpose this proposal is fulfilled with the purpose of solving the problems of electrical energy quality, seeking to reduce economic losses $ 90,003.76 and thereby improve the levels of standards that are considered normal according to the limits allowed in the current regulation.